1998
DOI: 10.1109/7.640285
|View full text |Cite
|
Sign up to set email alerts
|

Biased PNG law for impact with angular constraint

Abstract: A new homing guidance law is proposed to impact a target with a desired attitude angle. It is a variation of the conventional proportional navigation guidance (PNG) law which includes a supplementary time-varying bias. The proposed guidance law does not require a time-to-go estimation and has a simpler form. Analytic conditions for fulfilling the guidance goal are also provided. Simulation results demonstrate that the proposed guidance law has wider launch envelopes than the previous one and shows a good perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Although a number of papers considering IACG have been published [2][3][4][5][6][7][8], only a few papers related to ITCG is available in open literature. In [9], a suboptimal guidance law is proposed to control the impact time against a stationary target, which can be applied to a salvo attack of antiship missiles.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of papers considering IACG have been published [2][3][4][5][6][7][8], only a few papers related to ITCG is available in open literature. In [9], a suboptimal guidance law is proposed to control the impact time against a stationary target, which can be applied to a salvo attack of antiship missiles.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is formulated as a linear quadratic control problem. Later, a biased proportional navigation guidance (BPNG) law, proposed by Kim et al [2], had an extra term for annulling the terminal impact angle together with the conventional line-of-sight (LOS) rate term for lateral acceleration command. The BPNG law expanded the capturability region obtained by Kim and Grider [1] considerably, but when applied to maneuvering targets, gave moderate impact angle errors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is shown that for general MIMO missile engagements, a multi-input autopilot scheme can achieve a better homing performance than the single-input autopilot configuration. The theorem is illustrated using an exo atmospheric dual control missile [10][11][12][13] test case, where it is required to intercept the target at a predetermined impact angle [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%